Detection of Neisseria gonorrhoeae in the pharynx and saliva: implications for gonorrhoea transmission. (30th November 2015) - Chow, Eric P F; Lee, David; Tabrizi, Sepehr N; Phillips, Samuel; Snow, Anthony; Cook, Stuart; Howden, Benjamin P; Petalotis, Irene; Bradshaw, Catriona S; Chen, Marcus Y; Fairley, Christopher K
Abstract : Objectives: This study aimed to determine the proportion of untreated pharyngeal swabs or saliva samples positive by culture or nucleic acid amplification tests (NAATs) for Neisseria gonorrhoeae up to 14 days after an initial culture-positive pharyngeal swab. Methods: Men who have sex with men who tested positive for pharyngeal gonorrhoea at Melbourne Sexual Health Centre (MSHC) and returned to MSHC for treatment within 14 days between 13 October 2014 and 25 March 2015 were included in this study. Pharyngeal swabs and saliva samples were collected for culture and NAAT. Results: Of 33 initially culture-positive pharyngeal swabs, 32 saliva samples and 31 pharyngeal swabs were positive by NAAT and 14 pharyngeal and 6 saliva samples were positive by culture within 14 days. There was a significant decline in the proportion of repeated pharyngeal culture samples positive by culture over time (p<0.001). Conclusions: The rapid decline suggests pharyngeal gonorrhoea is short-lived, and the finding of gonorrhoea commonly in the saliva implicates this body fluid in its transmission without direct throat inoculation.